Assessment of Physical Working Capacity of Differently Trained and Aged Female Aerobic Gymnasts (Baltic Journal of Sport and Health Sciences, 2012)
Research background and hypothesis. Physical working capacity by PWC 170  test allows estimating physical preparation of athletes’ bodies, but these indices may not be directly linked to their sports achievements.Research aim. The aim of this study was to identify and assess physical working capacity characteristics of differently trained and aged female athletes. Research methods. The study included 40 subjects: young athletes (juniors) (12–14-years-old girls) and students of Lithuanian Academy of Physical Education – studying in aerobic gymnastics specialization. According to performance (training) level they were divided into the following groups: juniors (n = 10), beginners (n = 10), moderately trained (n = 10) and well-trained (n = 10) representatives of aerobic gymnastics. The testing included anthropometric measurements, heart rate (HR) measurements (HR values were recorded using heart rate measuring device “Sigma PC-15”, Germany), and PWC 170  tests. Athletes carried out two loads of physical activity at different intensities with a duration of 3 and 5 minutes (the rate of stepping (30 times per minute) was regulated according to the tempo of music that was specially prepared in the recording studio).Research results. We found that the differences in physical working capacity between well trained gymnasts and the beginners were not statistically significant. We established similar values of PWC 170   in moderately trained and junior groups; statistically significant difference (p  < 0.05) was established only comparing the latter two groups with well-trained athletes.Discusion and conclussions. The results showed that physical working capacity of well trained aerobic gymnastics athletes (participating in international competitions, world and European Championships) had not reached very high training level, but they were assessed as adequately trained. Physical working capacity of beginners was satisfactory and the indices of moderately trained  (with twice more  training and  competition experience) and junior athletes were very low.Keywords: aerobic gymnastics, physical working capacity, PWC170, heart rate.